Some Mechanical Properties of Retempered High Strength Concrete (University of Thi-Qar Journal for Engineering Sciences, 2013)
Iraq climate is characterized by the temperature increase during most of the months. The ambient temperatures are considered the most important factor that effects the production, properties and durability of the concrete. This study aims to evaluate the effect of retempering concrete after 60 minutes from cast by three different methods (retempring by water, retempring by Superplasticizer(G51) and retempring by remixing)on some of the mechanical properties of High Strength Concrete (HSC).In this work, different tests methods are adopted such as compressive strength, splitting tensile strength, ultrasonic pulse velocity and a hammer rebound Schmidt tests. These tests are investigated at different ages (7, 14, 28, and 56 days). The results show the high strength concrete that retempered by superplasticizer ) G51 leads to higher strengths, higher Ultrasonic Pulse Velocity (UPV) and higher hammer rebound than direct cast. The rate of increase in the mechanical properties of the high strength concrete that retempered by G51 relative to direct cast concrete at age 56 days were 28.29% ,16.37%, 2.76%,and 16.02% for compressive strength, splitting strength, Ultrasonic Pulse Velocity (U.P.V.) and hammer rebound respectively.While the concrete that retempered by water leads to lower strengths , lower Ultra Sonic Pulse Velocity (UPV) and lower hammer rebound than the other mixes.For the High Strength Concrete (HSC) mixes, the compressive strength and splitting tensile strength are closely related to UPV with a high correlation coefficient, R2.